Keberadaan komite pemantau risiko dalam pengawasan manajemen risiko perbankan untuk mewujudkan good corporate governance - ADRIATI, Septhia ([Yogyakarta] : Universitas Gadjah Mada, 2009)
This research is about the existence of risk monitoring committee in banking risk management supervision for good corporate governance. Risk management is the important issue in banking sector because Indonesia’s bank institution ever had a failure in manage the risk in 1997, and it makes economic crisis. Risk management supervisions must be performed by every person in bank management, especially by supervisory board which is the board of commissioner. Since the good corporate governance appears in banking business implementation, through Bank Indonesia Regulation, public bank need to establish risk monitoring committee to assist the commissioner performance related to risk management supervision in order to achieve good corporate governance. This research is of a juridical normative, which study and analysis are more on the secondary data collected from any related documents of the literature research. The secondary data are then corroborated with the primary data obtained from the field research, by using the interview guidance. Then, the analysis is based on the method of the qualitative descriptive. The result shows that risk monitoring committee which had been established by state-owned bank is more well-prepared in running the Bank Indonesia Regulations rather than the private bank. However, there are many obstacles which need to be completed from these two banks, which are charter committee formation and committee performance effectiveness . The expectations from the committee are form and complete the charter committee and encourage the committee performance which need support from the whole bank management, especially accommodation of the recommendations which given by the committee to the board of commissioner related to risk management supervision to good corporate governance achievement in banking company.